The effects of maternal body mass index (BMI) on the pregnancy outcome among primigravida who delivered at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang - Mohamed@Mohd Adnan, Siti Anisah (2012)
Objectives To measure the prevalence of antenatal, intrapartum and postpartum complications in the mother and the fetus/newborn in relation to their BMI. To determine the mean intrapregnancy weight gain for each BMI category. This is a cross sectional study conducted between December 2011 and November 2012. The study includes all primigravida who booked before 14 weeks of gestation. Upon delivery women had their antenatal, intrapartum and postpartum events reviewed and then categorized into five BMI groups; underweight (≤ 19.9 kg/m2), normal (20-24.9kg/m2), overweight (25-29.9kg/m2), obese (30-34.9 kg/m2) and morbidly obese (>35kg/m2). Women were followed up until discharged and reviewed again at 6 weeks postpartum. All statistical analyses were performed with the use of SPSS for Windows, version 18.0 (SPSS) and P-value of less than 0.05 was taken to be statistically significant Conclusion: The maternal risk increases as the BMI increases whereas the fetal risk increases with the extreme of BMI (underweight and morbidly obese). Inappropriate weight gain was observed in all groups but was significant in the morbidly obese.